How to compare performances of firms operating in different sectors? - FIRAT, SENİYE ÜMİT (TAYLOR & FRANCIS LTD, 2013)
This paper seeks to address the question How to measure different SMEs' performances comparatively?' An initial review reveals that the literature does not provide objective and explicit debate on the subject. Consequently, an approach is developed, informed by the literature, which is used to compare the performances of 37 SMEs. The consistency and reliability of the approach is tested, resulting in a ranking of the 37 firms according to their performances. Using cluster and factor analysis the paper demonstrates that leading indicators are somewhat redundant, and that lagging indicators have greater significance for the purpose of comparative measurement of different SMEs performances. Whilst the approach adopted here withstood internal and external validity tests and can be seen as a robust way of comparing SMEs performances, these results may be limited to this study.
Keywords: benchmarking; comparisons; measurement; performance; SMEs; MANUFACTURING PRACTICES; ORGANIZATIONAL PERFORMANCE; BALANCED SCORECARD; CONCEPTUAL-MODEL; BENCHMARKING; MANAGEMENT; CHAIN; INDUSTRY; IMPACT; SYSTEMS